THE USE OF IDIOMATIC LANGUAGE IN EXPRESSING DAILY SPEAKING STYLE THROUGH DRAMA FOR EFL STUDENTS - Novita Julhijah (STBA Pontianak, 2016)
Speaking is one of the important skills in learning English. Speaking means communication. One of the roles in communication is by using Idiom (an expression that cannot be understood from the meanings of its separate words but that has a separate meaning of its own). Idiomatic has roles in communication. This case study investigated on how to understand and use certain Idioms about daily life especially for their final project (DRAMA) by using essential methods that support the process in teaching. The participants were STBA Pontianak students’ class 1A1 at the second semester and the class consist of 40 students. The subject of this class is Conversation 2. There are more than 25 new idioms taught by the lecturer in one semester and as the last project was they should make a drama in a group consist of 5 to 6 students. The drama spent 3 to 5 minutes for each group and they should record it as their final assignment. The result of the research was amazing, many unexpected things happened, from the use of the idioms, and also the recording itself.